Bringing culture into the school Summary - Brandy Nothstine (Problemy Wczesnej Edukacji)
It is the teacher’s responsibility to make the classroom culturally responsive. Children bring their own culture to the classroom with them. The teacher needs to make sure these influences are nurtured in a positive way. The current literature indicates that language, social interactions, and play are all influenced by a child’s culture. The author used the Kendell multicultural checklist to highlight key areas of the classroom that needed to be addressed in order to make the classroom more culturally responsive. A plan was developed and put into practice to better understand family cultures and to better teach the children about different cultures. A culturally responsive classroom is critical for families and children to feel safe and welcome in a positive learning environment away from home. In the United States, 25% of children are immigrants or come from immigrant families (Souto-Manning 2013). This makes it crucial for educators to learn how to have a positive and welcoming multicultural classroom environment. With over 75% of early childhood teachers being white and speaking only English, it makes it that much more important for them to learn about different cultures and set up a classroom ready to nurture a variety of cultures (Souto-Manning 2013).